1989
DOI: 10.1530/jrf.0.0850331
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F-2  receptors in corpora lutea of pregnant rats and relationship with induction of 20 -hydroxysteroid dehydrogenase

Abstract: Summary. Luteal The present results suggest that PGF-2\g=a\,acting through a specific receptor site, is the physiological luteolytic signal. The consequence of its receptor binding seems to be the blockade of a gonadotrophic stimulus, which in turn determines (1) the decrease in progesterone synthesis and (2) the induction of 20\g=a\-hydroxysteroiddehydrogenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Indeed, inhibition of steroidogenesis does not initiate luteal regression or augment PRL-induced luteal regression in the hypophysectomized rat [58]. Similar to the current study, inhibition of FP receptor mRNA by PGF has been reported in sheep, cow, and human cells [59][60][61][62][63], and PGF binding to rat luteal cells is reduced following PGF treatment [64]. In contrast, Olofsson and colleagues [65] report that PGF increases FP receptor mRNA concentrations in rats.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, inhibition of steroidogenesis does not initiate luteal regression or augment PRL-induced luteal regression in the hypophysectomized rat [58]. Similar to the current study, inhibition of FP receptor mRNA by PGF has been reported in sheep, cow, and human cells [59][60][61][62][63], and PGF binding to rat luteal cells is reduced following PGF treatment [64]. In contrast, Olofsson and colleagues [65] report that PGF increases FP receptor mRNA concentrations in rats.…”
Section: Discussionsupporting
confidence: 81%
“…Another factor to be considered is a change in the sensitivity of the CL to PGF 2 with advancing gestation (Vermouth & Deis 1975, Khan et al 1979, Lahav et al 1988. Recent reports indicate that the number of PGF 2 binding sites increased with the age of the CL (Bussmann 1989, Orlicky et al 1992.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of PGF 2 induces abortion (Deis 1971), and induction of 20 -hydroxysteroid dehydrogenase (20 -HSD) activity (Pharriss & Wyngarden 1969, Strauss & Stambaugh 1974, Lamprecht et al 1975, Bussmann & Deis 1979, an enzyme that converts P 4 into a derivative devoid of progestational activity and considered a marker of luteolysis (Wiest 1968. The role of PGF 2 as an inducer of the physiological luteolysis in the rat is corroborated by the demonstration of specific receptors for PGF 2 on luteal membranes (Wright et al 1979, Bussmann 1989). Locally synthesised PGs have an important role in CL regression as indicated by an increase in the content of PGF 2 in the CL during spontaneous luteolysis (Olofsson & Selstam 1988).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…E2 also modified the expression of anti-apoptotic BCLl-2 and pro-apoptotic BAX (BCL2-associated X protein) genes, which are critical regulators of cell survival and death . During mid-pregnancy in rats, E2 is required for luteal survival, whereas at the end of pregnancy, high serum concentrations are responsible for increased synthesis of prostaglandin F2α and luteal expression of prostaglandin F2α receptors in association with functional regression of the corpora lutea (GIBORI et al, 1984;BUSSMANN, 1989;MCLEAN et al, 1989;. The findings support the premise that this E2 plays important roles in female reproduction.…”
Section: Introductionsupporting
confidence: 64%